Factorial analysis on nitric acid pretreatment of oil palm frond bagasse for xylan recovery - Nurul Aishah, Mazlan; Kamaliah, Abdul Samad; Nur Diyana, Yahya; Rozaimi, Abu Samah; Hafizuddin, Wan Yussof (Elsevier, 2019)
Hemicellulose in agricultural biomass are composed mainly of xylan which can be used for various application of valuable products including xylooligosaccharides. The aim of this work is to study the factors affecting acid pretreatment of oil palm frond bagasse for xylan recovery. The half fractional two-level factorial design with five factors was selected for the experimental design. The studied factors were nitric acid concentration (0.1 - 1.0%), temperature (37 - 90 °C), time (6 - 24 hours), solid loading (5 - 20%) and agitation (yes/no). The highest concentration of xylan at 0.5 g/L was obtained during pretreatment at 37 °C for 24 hours with 5% solid loading and 0.01% acid concentration without agitation. Among the factors involved, temperature was determined as the most significant factors in increasing xylan concentration followed by solid loading, time, acid concentration and agitation. The significant equation model represented in this study with the coefficient of determination (R2) of 0.9909 demonstrated that the experiment was successful. High xylan concentration obtained in this study proved that the use of dilute nitric acid for OPFB pretreatment is significant to preserve and recover xylan in biomass.